Synthesis of fivefold stellate polyhedral gold nanoparticles with {110}-facets via a seed-mediated growth method - Chen, Xiaodong (2014)
New Type of Gold Nanoparticle: A new class of fivefold stellate polyhedral gold nanoparticles (FSPAuNPs) with {110} facets have been synthesized by a seed-mediated growth method without adding surfactant. The size of FSPAuNPs can be simply adjusted from nanoscale to microscale by varying the amount of seeds, which results in a shift of the surface plasmon resonance peak from the visible to the NIR range.